Social Construction of Religious Attitude towards Disaster among Victims of Natural Disasters in Palu and Lombok - Ridho, Miftahur; Hudriansyah, Hudriansyah (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Every religion has teachings related to the best ways to cope with problems, including those caused by natural disasters. Thus, natural disasters can reshape the construction of religious attitudes among the community. Therefore, this research aims to understand how natural disasters are perceived by religious leaders in the aftermath of earthquakes in Palu and Lombok and how these perceptions impact the community's views on ideal religious attitudes after a disaster. This research employs a phenomenological approach with thematic data analysis techniques applied to research data collected through interviews with various religious leaders and community members in Lombok Island and Palu City, two regions that experienced natural disaster events in 2018. The research findings suggest that, despite the resurgence of a back-to-nature sentiment following the disasters in Lombok, for the Wetu Telu Muslim community, this sentiment carries a deeper meaning than merely promoting an environmentally conscious way of life. It signifies a return to a way of life rooted in traditions passed down through generations, a way of life that has been eroded by the modernization brought about by the proselytizing efforts of the majority Muslim group over the past five decades. In Palu City, the earthquake and tsunami disaster in 2018 has also shaped the community's perception of disasters and influenced their religious behaviors in the post-disaster society. In general, three common perspectives were identified. First, a majority believes the disaster is a form of divine admonition from Allah due to various deviant behaviors in the society. Second, some believe the disaster is a result of the shifting of the Palu-Koro fault plates, an unavoidable natural event, grounded in empirical knowledge sources and disaster facts. Third, Muslim groups view the disaster as a test from Allah. These three perspectives have essentially shaped a unique religious attitude among the community expressed in various forms of religiosity.